The Economy of Oil palm smallholders in Post-Conflict Aceh - Akmal, M; Bobby Rahman; Zulhilmi; Irfan; Teuku Muzaffarsyah (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Abstract. This article aims to describe the economy of oil palm smallholders in post-conflict Aceh. The data for this study were gathered through observation, interviews, and a review of the relevant literature. This study found that oil palm plantations were one of the industries that helped the people of North Aceh get back on their feet economically after the conflict. The peaceful conditions in post-conflict Aceh propelled the former GAM combatants to plunge into the oil palm plantation sector because the potential for land was quite wide. The success of the oil palm plantation activities by former GAM combatants encouraged the community to participate in planting oil palm so that the area of oil palm plantations continued to increase in North Aceh, and then the community's economy also increased. These conditions strengthened peace because GAM combatants successfully switched from conflict-related activities to economic ones.